Collaborative conservation at CSU: where are we now and where should we go? - Reid, Robin, speaker; Unidentified speaker (Colorado State University. Libraries, 2014)
Colorado State University has tremendous strengths in collaborative governance and conservation across campus. We started the Center for Collaborative Conservation 6 years ago to build upon and magnify that strength. In the process, we created a set of programs that attempt to build the ability of students, faculty and conservation practitioners to be more successful in collaborative efforts. Please come to this short seminar and long discussion to suggest how we might go forward together to take collaborative governance and conservation at CSU to even higher levels.
Presented at the Spring 2014 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Innovations in Communities around the World", March 25, 2014, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Robin Reid is the Director of the Center for Collaborative Conservation, an initiative of CSU's Warner College of Natural Resources. As Director, she oversees all the CCC's programs and staff. Robin has also been a senior research scientist at Colorado State's Natural Resource Ecology Laboratory since 2002, and is on the faculty of the Department of Human Dimensions of Natural Resources and the Department of Forest and Rangeland Stewardship. As faculty, she leads and participates in trans-disciplinary teams working on linked social-ecological systems, collaborative research methods, education and engagement in the drylands of East Africa and Mongolia. She also has a strong interest in linking and fostering learning about the collaborative conservation initiatives in the American West.
Recorded speech.
Accessibility features: Unedited transcript.